A\Political Cul-de-sac: CPI(M)'s Tragic Denouement - Sumanta Banerjee (Economic & Political Weekly EPW october 18, 2008, 2008)
The Communist Party of India (Marxist) has morphed into a Janus-like party, with one face as an opposition mouthing rhetoric against the neoliberal model of industrial development at the national level, and the other as a ruling power in three stateswhere they impose the same oppressive model. It is doubtful whether the present leadership can revive the spirit or restore the path that was charted in its party programme in 1964